Pengelolaan Keuangan Mahasiswa Penerima Beasiswa KIP-Kuliah: Perspektif Mahasiswa FEB Universitas Mataram - Putri, Dhea Mayzulianda; Isnawati, Isnawati (Jurnal Akuntansi, 2025)
This study aims to analyze the financial management of students who have received the Indonesia Smart College Card (KIP Kuliah) scholarship at the Faculty of Economics and Business, University of Mataram. The methodology that researcher use is a descriptive qualitative study, with data collected through in-depth interviews and observations of 100 students, both scholarship recipients and non-recipients. The results of this interview indicate that the phenomenon of a consumptive lifestyle among KIP Kuliah scholarship recipients affects their financial management, as many tend to allocate funds in ways that do not align with their academic needs. Additionally, delays in fund disbursement exacerbate students' financial planning difficulties, prompting them to seek additional income and potentially divert funds from their intended educational purposes. A literature review supports these findings, stating that a lack of financial education and weak behavioral control worsen the situation, making it difficult for students to distinguish between needs and wants. This study presents novelty by identifying inefficient financial management patterns and providing recommendations for improving the KIP Kuliah scholarship program.